Germline Variants That Affect Tumor Progression. Issue 5 (May 2021) - Chatrath, Ajay; Ratan, Aakrosh; Dutta, Anindya
Abstract : Germline variants have a rich history of being studied in the context of cancer risk. Emerging studies now suggest that germline variants contribute not only to cancer risk but to tumor progression as well. In this opinion article, we discuss the initial discoveries associating germline variants with patient outcome and the mechanisms by which germline variants affect molecular pathways. Germline variants affect molecular pathways through amino acid changes, alteration of splicing patterns or expression of genes, influencing the selection for somatic mutations, and causing genome-wide mutational enrichment. These molecular alterations can lead to tumor phenotypes that become clinically apparent such as metastasis, alterations to the immune microenvironment, and modulation of therapeutic response. Overall, the growing body of evidence suggests that germline variants play a larger role in tumor progression than has been previously appreciated and that germline variation holds substantial potential for improving personalized medicine and patient outcomes. Highlights: The differences in somatic aberrations between tumors can partially be explained by a patient's germline variants, suggesting that germline variants influence the somatic mutational landscape of cancer. Germline variants are associated with patient outcome across a large array of cancers. This suggests that germline variation is clinically relevant in the context of tumor progression. Molecularly, germline variants can affect tumor progression through amino acid changes, alteration of splicing patterns or expression of genes, influencing the selection for somatic mutations, and causing genome-wide mutational enrichment. Germline variants affect molecular and clinical phenotypes, such as genome instability, proliferative signaling, metastasis, alterations to the immune microenvironment, and modulation of therapeutic response and side effects. The smaller patient cohorts required to identify germline variants that affect tumor progression and patient outcome provide an outstanding opportunity to accelerate the identification and validation of clinically useful germline variants.